Organic Waste Reduction Strategy through Maggot Cultivation and Composting In Kota Pari Village - Purba, Renti Eva; Humairoh, Syahfitri; Angginta, Teguh; Akbar, Muhammad Fazlan; Octaviani, Putri (LPPM Institut Pendidikan Nusantara Global, 2025)
Kota Pari Village is a developing village or can be categorized as an independent village. Waste is one of the problems experienced by this village. Waste generation in this village mostly comes from household waste which is a type of organic waste and the low level of public knowledge about waste management, especially organic waste, further exacerbates the situation in Kota Pari Village so that the waste problem becomes more complex and needs to be addressed immediately. The purpose of this activity is to carry out waste management through the use of insects (maggot cultivation) and microorganisms (composting) to reduce organic waste generation. This activity was carried out on June 1, 2024 until October 30, 2024. The methods used were identifying problems, conducting socialization, preparing containers and materials and training. The community that participated in this program showed a very good reaction and participated in all series of activities actively. The cultivation of maggot and composting of organic waste that has been carried out can foster community awareness in managing organic waste properly and can be a solution and strategy in reducing organic waste in the village environment.